2014
DOI: 10.3224/zff.v26i3.18993
|View full text |Cite
|
Sign up to set email alerts
|

Sibling structure and educational achievement: How do the number of siblings, birth order, and birth spacing affect children’s vocabulary competences?

Abstract: Empirical evidence suggests that sibling structure influences children’s educational outcomes: While the negative effect of the number of siblings is quite consistent, there are mixed findings for birth order and birth spacing. According to the resource dilution hypothesis, differences between siblings occur because siblings have to share family resources. Having a larger number of siblings, being a later-born child as well as narrow age gaps between siblings can affect the parental resources available for eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
2
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 30 publications
(90 reference statements)
2
12
2
1
Order By: Relevance
“…The present study found a compensatory effect of a high social origin with respect to track attendance but not with respect to cognitive skills. The findings for cognitive skills are at odds with the results of Karwath et al (2015), who reported a concentration of the negative association between birth order and children's vocabulary skills in socioeconomically disadvantaged families but did not use family fixed-effects models. Barclay (2015b), who used family fixed-effects models and Swedish register data, found, however, in line with my results, no socioeconomic differences in the effect of birth order on intelligence.…”
Section: Discussioncontrasting
confidence: 93%
See 2 more Smart Citations
“…The present study found a compensatory effect of a high social origin with respect to track attendance but not with respect to cognitive skills. The findings for cognitive skills are at odds with the results of Karwath et al (2015), who reported a concentration of the negative association between birth order and children's vocabulary skills in socioeconomically disadvantaged families but did not use family fixed-effects models. Barclay (2015b), who used family fixed-effects models and Swedish register data, found, however, in line with my results, no socioeconomic differences in the effect of birth order on intelligence.…”
Section: Discussioncontrasting
confidence: 93%
“…Barclay (2015b) found, using family fixed-effects models and data on Sweden, no socioeconomic differences in the effect of birth order on intelligence among brothers. Contrary to that, Karwath et al (2015) found, using data on a small region in Germany and not employing family fixed-effects models, a negative association between a higher birth order and vocabulary skills for children from less educated families but not for children from highly educated families. With respect to educational attainment, previous research based on withinfamily variation found no differences in birth order effects by maternal education in Norway (Black et al 2005) or by parental occupational status and education in Germany (Härkönen 2014).…”
Section: Variation Of the Impact Of Sibling Characteristics On Education By Family Backgroundcontrasting
confidence: 89%
See 1 more Smart Citation
“…At the household level, many studies, mostly in sociology, have found that the number of siblings exerts a negative effect on each child's educational attainment, including grade completion and test scores (Conley & Glauber, 2005;Karwath, Relikowski, & Schmitt, 2014). In one extensive study across various samples, Blake (1989) finds the "dilution effect": more siblings dilute a child's allocation of parental resources.…”
Section: Number Of Siblings and Educational Attainmentmentioning
confidence: 99%
“…Child's gender may also influence parental involvement (e.g., Lundberg, 2005;Raley & Bianchi, 2005). Older children are shown to receive higher educational scores than younger ones (e.g., Karwath et al, 2014) and children's age tends to influence also parental involvement (Waldfogel, 2006). When the number of siblings in household increases, the amount of time parents are able to invest in any particular child tends to decrease (e.g., Downey, 2001;Coleman, 1988).…”
Section: Other Relevant Factorsmentioning
confidence: 99%